2011
DOI: 10.1107/s1600536811021325
|View full text |Cite
|
Sign up to set email alerts
|

2-(4-Fluorophenyl)-3-methyl-1H-indole

Abstract: The indole N—H hydrogen in the title compound, C15H12FN, does not display classical hydrogen bonding. Rather it forms an interaction with the π system of an adjacent indole, resulting in weakly inter­acting chains along the [001] direction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The presence of N-HÁ Á Á interactions in indole complexes with aromatic species has been investigated by IR spectroscopy (Muñ oz et al, 2004), and such bonds have also been observed in many crystal structures of indole derivatives (e.g. Krishna et al, 1999;Cordes et al, 2011).…”
Section: Chemical Contextmentioning
confidence: 99%
“…The presence of N-HÁ Á Á interactions in indole complexes with aromatic species has been investigated by IR spectroscopy (Muñ oz et al, 2004), and such bonds have also been observed in many crystal structures of indole derivatives (e.g. Krishna et al, 1999;Cordes et al, 2011).…”
Section: Chemical Contextmentioning
confidence: 99%